RETRACTED: Impact of Financial Literacy on Investors: A systematic literature review using PRISMA protocol - Shunmugasundara, V.; Maurya, Ritika (Nepalese Journal of Management Science and Research, 2023)
The article “Impact of Financial Literacy on Investors: A Systematic Literature Review Using PRISMA Protocol” in Vol.6(1) 2003 of the Nepalese Journal of Management Science and Research was RETRACTED on 9th July 2026.This was done because the article had already been published in another journal prior to its publication in the Nepalese Journal of Management Science and Research.